Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How do I use partial fractions for the expression $\dfrac{t+1}{2\sqrt{t}(t-1)}$? Because I have to find the integral of it... Thank you

share|cite|improve this question
Partial fractions are a device that is helpful with rational functions. Your function isn't. I suggest first a substitution. (You will not find constants $a,b,c$ that work.) – André Nicolas Jul 14 '13 at 13:51
It's a rational function of $\sqrt{t}$. – Michael Hardy Jul 14 '13 at 16:43
up vote 4 down vote accepted

Your given integrand isn't a rational function (yet) to use partial fractions, we must first obtain a ratio of polynomials. We can do this by substituting $u = \sqrt t$.

$$u = \sqrt t \implies t = u^2 \implies dt = 2u\,du$$

Now, substituting the above into our original integral gives us:

$$\int \frac{t+1}{2\sqrt{t}(t-1)}\,dt = \int \frac{u^2 + 1}{2u(u^2 - 1)}\,(2u\,du) =\int \dfrac {u^2 + 1}{u^2 - 1}\,du$$

Now, polynomial division, followed by "partial fractions" gives us: $$\int \left(1 + \dfrac {1}{u^2 - 1}\right)\,du = \int \left(1 + \dfrac {1}{(u-1)(u+1)}\right)\,du = \int \left(1 + \dfrac{A}{u - 1} + \dfrac B{u + 1} \right) \,du$$

Now we solve for $A, B$:

$A(u+1) + B(u - 1) = 2 \iff Au + A + Bu - B = 2 \iff (A + B)u + (A - B) = 2$

$A + B = 0$
$A - B = 2$

Adding the equations gives us $2A = 2 \iff A = 1 \implies B = -1$ and we'll have a result of the form $$u + A\ln|u-1| + B\ln |u+1| + \text{Constant}$$ $$ = \sqrt t +\ln|\sqrt t - 1| - \ln |\sqrt t + 1| + \text{Constant} $$ $$ = \sqrt t+ \ln\left|\dfrac{\sqrt t - 1}{\sqrt t+1}\right| + C$$

share|cite|improve this answer

We can easily do the fraction as you said, but I suggest to set $\sqrt{t}=u$ first and then think about the converted integral. Indeed, you will get the following integral instead after changing the variables:

$$\int \frac{t+1}{2\sqrt{t}(t-1)}dt\longrightarrow \int\frac{u^2+1}{2u(u^2-1)}\times 2u\,du$$

share|cite|improve this answer

Hint: Try writing $t-1=(\sqrt{t}-1)(\sqrt{t}+1)$ and $t+1=(t-1)+2$, and using the substitution $w=\sqrt{t}$.

share|cite|improve this answer

Let $x=\sqrt{t}$ so $dt =2xdx$ and

$$\int\frac{t+1}{2\sqrt{t}(t-1)}dt=\int\frac{x^2+1}{(x^2-1)}dx=\int dx+\int\frac{2}{x^2-1}=\int dx+\int \frac{dx}{x-1}-\int \frac{dx}{x+1}\\ =x+\ln|x-1|-\ln|x+1|+C=\sqrt{t}+\ln|\sqrt{t}-1|-\ln|\sqrt{t}+1|+C$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.